2011
DOI: 10.1002/jmv.22020
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of G9 as a predominant genotype of human rotaviruses in Cuba

Abstract: To study human rotaviruses in Cuban children up to 5 years old with acute diarrhea, a total of 64 faecal samples from two pediatric hospitals between 2006 and 2008 were analyzed. Thirty-nine samples (60.9%) were found positive for rotaviruses by enzyme-linked immunosorbent assay (ELISA) and polyacrylamide gel electrophoresis (PAGE), while four (6.2%) exhibited discordant results (ELISA positives/PAGE negatives). All the positive samples were genotyped by a reverse transcription-polymerase chain reaction (RT-PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
12
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 50 publications
6
12
1
2
Order By: Relevance
“…Studies based on the molecular characterization of RVA into G and P genotypes in the Caribbean are scarce. However, similar to our findings in Haiti, the Dominican Republic, 13,14 St. Vincent, 15 and Cuba 16 have all reported G1P [8] as the most common strain in circulation, followed by G9P [8]. The detection of genotype G12 for the first time in Haiti further confirms the emergence of this genotype globally.…”
supporting
confidence: 90%
“…Studies based on the molecular characterization of RVA into G and P genotypes in the Caribbean are scarce. However, similar to our findings in Haiti, the Dominican Republic, 13,14 St. Vincent, 15 and Cuba 16 have all reported G1P [8] as the most common strain in circulation, followed by G9P [8]. The detection of genotype G12 for the first time in Haiti further confirms the emergence of this genotype globally.…”
supporting
confidence: 90%
“…Extensive molecular epidemiological studies globally have indicated that G1 is the most common circulating genotype. Similarly, the predominance of G1 genotype of rotavirus was observed in our study (52.27%), which is in concordance with the results of genotyping from different parts of the world including: Swiss (Lacroix et al, 2010), Taiwan (Mast et al, 2010), France and Cuba (Ribas et al, 2011). Although G2 and G3 are among the most prevalent rotavirus genotypes worldwide (Fang et al, 2005;Dey et al, 2009;Wang et al, 2009;Jere et al, 2011), Kargar et al 2939 nonetheless this strains were not detected in this study.…”
Section: Discussionsupporting
confidence: 92%
“…However, G4 was detected only in 2.27% of all children with rotavirus gastroenteritis. Recently, G9 has appeared as the common genotype in Albania (Annarita et al, 2010), Cuba (Ribas et al, 2011) and other countries (Van Damme et al, 2007;Nelson et al, 2008), but in this study only four (4.54%) G9 genotype isolate were identified. The emergence of G9 as an important genotype in developing and industrialized countries necessitates the inclusion of G9 in future rotavirus vaccines.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The role of this technique in the diagnosis of giardiasis is subject of controversy; some studies favour this technique; 26,27 however, in others, the results are poor. 28 Although we have not got any evidence which supports the following hypothesis, one of the reasons why only small percentage of practitioners ordered faecal smear examination to a high proportion of cases reporting diarrhoea and vomiting at first consultation could have been that, according to their awareness, illness should have been caused by a viral gastroenteropathic pathogen [29][30][31][32] and treated children accordingly, and also their failure to consider giardiasis, especially under the acute diarrhoeal disease context. As viral infections are most frequent, testing for protozoa is not routinely performed for patients with acute gastroenteritis, because it adds cost without substantially altering treatment.…”
Section: Discussionmentioning
confidence: 92%